PENERAPAN MEMBRAN FILTRASI DARI SELULOSA ASETAT DAN CHITOSAN UNTUK PRODUKSI BERSIH PADA INDUSTRI PULP DAN KERTAS - Suprihatin, Muhammad Romli dan Andes Ismayana (Department of Agroindustrial Technology, Bogor Agricultural University, 2004)
ABSTRACTCleaner production is currently considered as a strategic element in manufacturing technology. The application of cleaner production is focused on the reduction or elimination of environmental pollution in their sources, and in the same time in increasing the effectiveness and efficiency of the resource utilization in industrial processes. The objectives of this research were to produce and characterize membranes from natural polymers (cellulose acetate and chitosan), (ii) to test the performance of the produced membrane for cleaner production (wastewater reuse/recycling) in pulp and paper industry as a case study, and ( iii) to evaluate the technical and economical feasibility of the membrane application in the field. Results have shown that a relative high flux of 100 L/m2hr was achieved with the chitosan membrane, which is comparable with the flux of commercial available membranes. The flux of the produced cellulose acetat membrane was relative lower, namely app. 33 L/m2hr. Turbidity, color and COD (chemical oxygen demand) of the wastewater could be reduced up to 80 - 96 percent, 77 - 99 percent, and 35 - 52 percent respectively, depending on wastewater characteristics, type of the membrane material, and the operating conditions. Based on the measured parameters it is possible to reuse or recycle the treated effluent of the pulp and paper industry by using the membrane filtration. Costs for the membrane material (polymer) were Rp 5.525,-/m2 for the cellulose acetate membrane and Rp 15.000,-/m2 for the chitosan membrane. The material cost for production of microbial cellulose acetate membrane seems to be too expensive, because one kg of dryed microbial cellulose self cost Rp 250.000,-, while commercial cellulose acetat cost only Rp 85.000,-/kg.Key words: cleaner production, membarne filtration, wastewater, pulp and paper industry